PENGARUH ENTREPRENEURIAL ORIENTATION, CULTURE ORGANIZATION INTERNAL FACTOR TERHADAP PERFORMANCE ORGANIZATION MELALUI CORPORATE ENTREPRENUERSHIP CAPABILITY PADA UMKM BATIK TULIS DI JAWA TIMUR - Chandra Kartika (Kompetensi (Competence : Journal of Management Studies), 2017)
This research aims to provide a paradigm change creative businessmen in order to develop business in the manage well with using some variables entrepreneurial orientation, culture organization, internal factor in increasing permormance organization through corporate entrepreneur capability and can increase the level of a large proportion of with the development of entrepreneurial character on the whole community of  UMKM Batik in East Java. Researchers attempting to help to resolve the problems that the economy is still not Optimal yet on the community of UMKM Batik in East Java and an increase in the creative economy that synergy in improve business kinierja in an organization of UMKM Batik in East Java, so that the income level of UMKM Batik in the lands around East Java can rise again. Researchers took samples around 100 people entrepreneurs who have a business UMKM Batik in East Java and using the methods of quantitative analysis and using the appliance  SEM AMOUS analysis and location is specified in the researchers,) is expected to found a positive result against the business development of  UMKM Batik and can help the sales profit level and can improve the level of technology used by entrepreneurs and increase the level of community welfare UMKM Batik in East Java. And to increase the performance of the organization of UMKM Batik in East Java.